Tingkat Persepsi dan Ketertarikan Masyarakat Dalam Aktivitas Fisik Berirama Dalam Menjaga Kebugaran Fisik - Firdaus Hendry Prabowo Yudho; Mela Aryani; Adi Rahadian; Asep Ramdan Afriyuandi; Andi Kurniawan Pratama (JTIKOR (Jurnal Terapan Ilmu Keolahragaan), 2020)
This research is motivated by researchers' curiosity about the perception and interest of the community to carry out general sports and rhythmic movement activities. The aim is to get a comprehensive and sufficient picture so that further research can be carried out in the future in creating a physically active and fit community. The study used survey methods for 5 categories of rhythmic activity that were popular in the community, namely SKJ Exercise, Low Impact Aerobics, High Impact Aerobics, Healthy Heart Exercise / Elderly, Zumba, and Dangdut Exercise. The conclusion of this study revealed a sufficient level of interest from the community towards Rhythmic activity as one of the interesting activities to maintain body fitness with the results that the average female respondents preferred rhythmic activity in general compared to male respondents.